Doping in sport climbing: Status quo in a new Olympic discipline - Lutter, C.; Tischer, T.; El-Sheikh, Y.; Schöffl, V. (Current Sports Medicine Reports, 2019)
Sport climbing was recently selected to be part of the 2020 Olympic games in Tokyo, which is a significant step in the sport`smaturation process. Although this is an exciting development for most athletes, coaches, and fans of the sport, this new status of sport climbing comes withmore responsibility. With growing pressure to perform on the world stage, sport climbing athletes may become more susceptible to the pressures of doping. The term "rock climbing" is commonly used to refer to all aspects of the sport, but it is important to understand that there are several subdisciplines that are quite different in terms of physical demands and sport environment.Modern competition sport climbing and bouldering are performed on artificial walls. Outdoor "sport climbing" (aka rope climbing) and "bouldering" (climbing short boulders with no rope) are performed on real rock and are considered the two main subdisciplines of sport rock climbing.